Political Influence of The Lebanese Diaspora in Côte D’ivoire Before the 2020 Elections - Shipilov, Alexander (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The recent political developments that took place in West Africa, encompassing several bloody civil wars and the following reconstruction, were marked by the involvement of a number of regional and completely external stakeholders. It has been, furthermore, broadly acknowledged by the recent scope of globalization, international, and transnational studies that diasporas constitute a significant portion of the internal groups of interest in local political processes. This tendency is true to West Africa and, most particularly, Côte d’Ivoire, the country that has experienced the latest large-scale civil conflict among the states in this part of Africa.